IMPROVING THE EFFICIENCY OF MİLİTARY LOGISTICS SYSTEM MANAGEMENT WITH THE INTRODUCTION OF INNOVATIVE TECHNOLOGIES - Yadigar, Alikhan (Collection of scientific papers «ΛΌГOΣ», 2025)
The article provides information on the negative impact of problems in military logistics management on the performance of combat missions, as well as on the changing nature of modern wars and the incompatibility of the classical material-technical support system with new operational and combat techniques and rules. The possibility of using information and communication technologies (ICT) in military logistics is considered in order to improve the existing logistics system and adapt it to the requirements of modern warfare.